PENDEKATAN AL-QUR’AN UNTUK MENINGKATKAN POLA PIKIR MENURUT HUDA ABDUL RAHIM MUHAMMAD QASIM MIMANY - Fatul Fauziah, Asmah Rohma; Azizah, Noris Aniqotul (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2024)
The Qur'an is a source of knowledge, which explains several fields of science and knowledge for mankind to think about. With reason, humans can utilize this reason by thinking, which will add new insights. The aim of writing this scientific work is to find out the Al-Qur'an approach to improving the mind according to Huda Abdul Rahim Muhammad Qasim Mimany. The method used in this research is the library method by collecting data sources from books, journals, articles and other references related to the research. Meanwhile, the data analysis used is content analysis. This research produced findings, namely: 1) The Qur'an explains how important it is to use the mind in achieving the goals of life on earth, which is explained in surah al-Baqarah verse 164 and surah an-Nahl verse 125. 2 ) Humans have five senses and conscience can help him to understand his environment, based on surah al-Jasiyah verse 13. Apart from that, human thought is a guide to knowing the truth and achieving the truth by carrying out his obligations and good deeds. 3) Allah SWT glorifies humans who think and have knowledge, because knowledge is the path to God, while reason is the part of humans who think, reflect, and through this gain knowledge. 4) The Qur'an as a source of knowledge, which explains several fields of science and knowledge for mankind. This research has enormous potential to make a positive contribution to various aspects of life. This research can be a basis for developing programs that are more effective in improving the quality of human life.